Follow-up of Law-Making State Institutions to the Legal Message of the Constitutional Court Decision: Tindak Lanjut Lembaga Negara Pembentuk UndangUndang terhadap Pesan Hukum Putusan Mahkamah Konstitusi - Iskandar Muda (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
Observing the follow-up of state law-forming institutions (House of Representative and President) after the Constitutional Court Decision is a wise step for the development of legal knowledge. This study uses a normative juridical approach. The results of the study: (i) legal order (injunction) in the ruling section, while legal order (advice) contained in legal considerations and, (ii) follow-up to legal order (injunction) contained in the Constitutional Court's rulings that have been implemented. and some have not been implemented because it has not reached the specified time limit. Meanwhile, the legal order (advice) of the related Constitutional Court decision has been implemented. In the end, it can be concluded that in a decision of the Constitutional Court there are two categories of legal order, namely injunction and advice, which have been implemented by the legislators. Although some have not been implemented because it has not reached the specified time limit.